Epidemiology and outcomes of hepatitis C infection in elderly US Veterans. Issue 9 (3rd April 2016) - El‐Serag, H. B.; Kramer, J.; Duan, Z.; Kanwal, F.
Summary: The chronic hepatitis C (CHC) cohort in the United States is getting older. Elderly patients with CHC may be at a high risk of cirrhosis and hepatocellular carcinoma (HCC), but also other nonhepatic comorbidities that negatively impact their likelihood of receiving or responding to antiviral treatment. There is little information on the clinical epidemiology or outcomes of CHC and its treatment in the elderly. We conducted a retrospective cohort study of 1 61 744 patients with a positive Hepatitis C virus RNA in the Veterans Health Administration Hepatitis C Clinical Case Registry to examine the association between age subgroups (20–49, 50–64, 65–85 years) and risk of cirrhosis, HCC or death using Cox proportional hazards models. We also examined the effect of treatment with a sustained viral response (SVR) on these outcomes in each age subgroup. The age distribution was 36.8% 20‐ to 49‐year‐olds, 57.6% 50‐ to 64‐year‐olds and 5.6% 65‐ to 85‐year‐olds (i.e. elderly). Risk of cirrhosis, HCC and death was significantly elevated in elderly patients [HR cirrhosis = 1.14 (1.00–1.29), HR HCC = 2.44 (1.99–2.99); HR death 2.09 (1.98–2.22)] compared with younger patients. The incidence of HCC was than 8.4 per 1000 PY in the elderly compared with 2.6 per 1000 PY and 5.7 per 1000 PY, among the 20–49 and 50–64 age groups, respectively. Elderly patients were significantly less likely to receive antiviral treatment (3.8% vs 14.8% and 19.1%, P < 0.0001), but among those who received treatment SVR was not different among the age groups (33.5% vs 33.2% and 32.1%). In an analysis limited to those who received treatment, SVR compared to treatment receipt with no SVR was associated with a reduction in risk of developing cirrhosis (HR = 0.34; 0.18–0.66) and HCC (HR = 0.60; 0.22–1.61) and all‐cause mortality risk (HR = 0.52, 0.33–0.82). Elderly patients with CHC are more likely to develop HCC than younger patients but have traditionally received less antiviral treatment than younger patients. However, receipt of curative treatment is associated with a benefit in reducing cirrhosis, HCC and overall mortality, irrespective of age.